In vitro treatments to improve the germination response in orophytic-boreal species from the northern Apennines - Casentine Forest National Park - SGARBI, Elisabetta; GRIMAUDO, Maddalena; DEL PRETE, Carlo; DALLAI, Daniele (2010)
The Botanic Garden of Modena and the Casentine Forest National Park recently promoted an integrated in situ/ex situconservation project. Researchers aimed to propagate certain plant species that grow in the Park, which have specificprotection requirements on account of their phyto-geographic importance. These species are: Hieracium villosum L.,Saxifraga oppositifolia L., Saxifraga paniculata Miller, Saxifraga moschata Wulfen. In this work, we present someuseful treatments for bypassing the natural dormancy of the seeds/achenes and for improving in vitro germination andgrowth.